Revitalisasi Gerakan Pembaruan Persatuan Persis (Persis) - Ali Usman (Kopertais Wilayah III Yogyakarta, 2021)
This article describes the work of Persatuan Islam (Persis) as an Islamic organization that was born in 1923 in Bandung. Exactly, like Muhammadiyah, is a reformer group in which it has a distinctive religious outlook, founding figures, and strategies to develop organizational symbols. However, unlike Muhammadiyah, including Nahdlatul Ulama (NU), which is growing rapidly, Persis is experiencing delays, running slowly. This can be observed through at least three roles: political movements, cultural da'wah, and educational institutions. In this qualitative research based on library research, it is necessary to revitalize. It is necessary to evaluate and reflect on their work so far, starting with religious doctrine, distribution of cadres in the socio-political field, and the development of educational institutions. Keyword: Persistence, Renewal, Movement Revitalization